Nutritional Status of Inmates in the Central Prison of Mbuji-Mayi, Democratic Republic of Congo - Patoka Guillaume Kalonji Muasa; De Coninck Gérard; Okenge Ngongo Léon; Ilunga Ilunga Félicien; Albert Adelin; Giet Didier (International Journal of Nutrition, 2021)
Background The nutritional situation in prisons of developing countries and the health status of inmates remain a major human rights concern. The objective of the study was to assess the nutritional status of inmates jailed in a prison of the Democratic Republic of Congo (DRC). Methods This cross-sectional study was conducted over a 4-month period in the Central Prison of Mbuji-Mayi, DRC. Three hundred inmates were selected according to the Malnutrition Universal Screening Tool (MUST). Severe malnutrition was defined according to Buzby index and Nutritional Risk Index (NRI). Data were analyzed by Stata™ (version12.0). Results The inmates were aged between 18 and 70 years and primarily males (88.7%). Of them, 24% were suffering from severe malnutrition and 62% of moderate malnutrition as based on the NRI. At the time of study, 88% of inmates were incarcerated for more than 6 months. Multivariate logistic regression analysis showed that factors independently associated with severe malnutrition were incarceration of more than 6 months (OR=5.1; 95% CI (1.5-17.4)), origin of food (prison vs. family or NGO) (OR=4.7; 95% CI (1.6-13.8)) presence of tuberculosis, human immunodeficiency virus and/or intestinal infections (OR=2.6; 95% CI (1.4-4.7)). Conclusions The nutritional situation in the Central Prison of Mbuji-Mayi is precarious. There is urgent need to supply enough nutrient-rich food to improve health of inmates.
Keywords: health condition